Attenuation of Colistin Bactericidal Activity by High Inoculum of Pseudomonas aeruginosa Characterized by a New Mechanism-Based Population Pharmacodynamic Model - Bulitta, Jürgen B. (American Society for Microbiology (ASM), 2010)
Colistin is increasingly being utilized against Gram-negative pathogens, including Pseudomonas aeruginosa, resistant to all other antibiotics. Since limited data exist regarding killing by colistin at different initial inocula (CFUo), we evaluated killing of Pseudomonas aeruginosa by colistin at several CFUo and developed a mechanism-based mathematical model accommodating a range of CFUo. In vitro time-kill experiments were performed using ≥8 concentrations up to 64 × the MIC of colistin against P. aeruginosa PAO1 and two clinical P. aeruginosa isolates at CFUo of 10(6), 10(8), and 10(9) CFU/ml. Serial samples up to 24 h were simultaneously modeled in the NONMEM VI (results shown) and S-ADAPT software programs. The mathematical model was prospectively “validated” by additional time-kill studies assessing the effect of Ca(2+) and Mg(2+) on killing of PAO1 by colistin. Against PAO1, killing of the susceptible population was 23-fold slower at the 10(9) CFUo and 6-fold slower at the 10(8) CFUo than at the 10(6) CFUo. The model comprised three populations with different second-order killing rate constants (5.72, 0.369, and 0.00210 liters/h/mg). Bacteria were assumed to release signal molecules stimulating a phenotypic change that inhibits killing. The proposed mechanism-based model had a good predictive performance, could describe killing by colistin for all three studied strains and for two literature studies, and performed well in a prospective validation with various concentrations of Ca(2+) and Mg(2+). The extent and rate of killing of P. aeruginosa by colistin were markedly decreased at high CFUo compared to those at low CFUo. This was well described by a mechanism-based mathematical model, which should be further validated using dynamic in vitro models.